AB0764 Radiographic Characteristics of The Hip May Predict Response To Viscosupplementation in Patients with Hip Osteoarthritis. Results of A Prospective Observational, Multicenter, Open-Label, Pilot Study. (15th July 2016) - Eymard, F.; Maillet, B.; Lellouche, H.; Conrozier, T.
Abstract : Background: Viscosupplementation by intra-articular injections of hyaluronic acid (HA) is used to alleviate pain and improve function in patients with hip osteoarthritis (HOA). However patients the more likely to be satisfied with the treatment are not well defined because predicive factors of success are still lacking. Objectives: To identify radiological predictive factors of response to viscosupplementation (VS) in patients with hip osteoarthritis (HOA). Methods: Prospective, multicenter, open-label trial, performed in daily practice conditions. Patients with hip OA were treated with a single IA injection of crosslinked HA+mannitol (CHAM), using fluoroscopy or ultrasonography guidance. Hip radiographs at baseline were scored by a single experienced observer using Kellgren-Lawrence (KL) grade and OARSI score for joint space narrowing (JSN), osteophytes and subchondral changes. Hips were classified according radiographic features such as JSN location (supero-lateral, supero-medial, axial, diffuse, posterior) and architectural abnormalities (dysplasia, coxa profunda, femoro-acetabular impigement FAI). Pain and function were assessed at baseline and day 90 using WOMAC index. Satisfaction with the treatment, decrease in analgesics consumption throughout the follow-up, and treatment efficacy were self-assessed by the patients at day 90. Association between these features and response to treatment (pain improvement>50% versus baseline) were assessed in univariate analysis, and then using logistic regression, adjusting confounded variables Results: One hundred patients (59 females, 41 males, mean age 62) were included in the trial. Hip OA was bilateral in 39 patients. The median (range) WOMAC pain and function at baseline were 26 (7–42) and 79 (9–134) respectively. Response to treatment was obtained in 60 patients without any difference regarding gender, age and BMI but was better in the most symptomatic patients (p=0.014). In the 80 patients who completed the trial with fully available radiographic and clinical data, efficacy was inversely related to KL grade (p=0.02). Furthermore the percentage of success was highly dependent on the radiographic features. Regarding JSN severity, response was obtained in 100%, 59%, 55%, 41% of the cases for grade 0, 1, 2 and 3 respectively. Regarding the femoral head migration, better results were obtained in axial (65%) and supero-medial (62%) JSN than in supero-lateral JSN (50%). Response was also more likely to be obtained in case of FAI (62%) and coxa profunda (69%) than in hip dysplasia (40%). Conclusions: This pilot study, which need further confirmation by larger scale trials, suggests that radiological features might be of high importance for the decision of viscosupplementation in patients with hip OA. Acknowledgement: The authors aknowledge LABRHA, SFR OA group and GRRIF for the grants and sponsoship. Disclosure of Interest: F. Eymard: None declared, B. Maillet: None declared, H. Lellouche Consultant for: Genevrier, Sanofi, T. Conrozier Consultant for: Laboratoire de rhumatologie Appliquée, Speakers bureau: Genevrier, Sanofi